2021
DOI: 10.3390/clockssleep3040044
|View full text |Cite
|
Sign up to set email alerts
|

Player Chronotype Does Not Affect In-Game Performance during the Evening (>18:00 h) in Professional Male Basketball Players

Abstract: Sport-specific skills display diurnal variation across various team sports such as badminton and tennis serving accuracy and soccer dribbling, volleying, and chipping execution. However, the effects of athlete chronotype on in-game sport-specific skill performance according to time of day across team sports is not well understood. Therefore, the aim of this study was to identify the effect of player chronotype on in-game basketball performance during evening games. Professional male basketball players (n = 11)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, variations in shooting scores between chronotype groups in the morning (small-large effects) and afternoon were not statistically significant (moderate-large effects) ( Pengelly et al, 2022 ). Pengelly et al (2021) identified the effect of player chronotype on in-game basketball performance during evening games. The study found that in-game performance appeared not to be affected by chronotype in evening games among professional male basketball players ( Pengelly et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, variations in shooting scores between chronotype groups in the morning (small-large effects) and afternoon were not statistically significant (moderate-large effects) ( Pengelly et al, 2022 ). Pengelly et al (2021) identified the effect of player chronotype on in-game basketball performance during evening games. The study found that in-game performance appeared not to be affected by chronotype in evening games among professional male basketball players ( Pengelly et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Pengelly et al (2021) identified the effect of player chronotype on in-game basketball performance during evening games. The study found that in-game performance appeared not to be affected by chronotype in evening games among professional male basketball players ( Pengelly et al, 2021 ). Gepfert et al (2020) investigated whether 5% body mass-resisted or assisted conditioning activity (CA) may improve 5 m slide-step performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the influence of chronotype on the diurnal variation in athletes' performance [9][10][11][12][13][14]. In [10], it was evaluated the influences of morning and evening sleep on varsity collegiate rowers' performance on two-leg muscle strength-demanding tasks.…”
Section: Impact Of the Circadian Rhythms On Performancementioning
confidence: 99%
“…Among professional male basketball players, performance in evening games was not affected by chronotype (i.e., morning vs neither). The author suggested that sports practitioners may not require to consider athletes' chronotypes when evolving competition approaches and conveying roles when dealing with more morning and neither-types [14].…”
Section: Impact Of the Circadian Rhythms On Performancementioning
confidence: 99%